Report on Power Compensation and Total Harmonic Distortion level Analysis - Nikita Ramesh Kalaskar; Rajesh Holmukhe (International Journal of Electrical and Computer Engineering (IJECE), 2016)
In the chart of Indian science based industry, pharmaceutical industry is on top position. So it is essential to fulfil such critical requirement or demand, production should be with high speed. For such high production, using of software based machineries, electronic circuits are been used. By using such electronic based equipment’s and machineries, it is obvious day by day increasing non-linear load of the industry which lead to lagging power factor. In electric system nonlinear load with low power factor draws more current from source. So because of such high current drawn, life of switchgear, wire and other electrical equipment decreases. So due to large equipment and wasted energy, the electrical utilities company usually charge a higher cost to industrial customer for the constant logging power factor. To improving the lagging power factor, industry may prefer to install capacitor bank in series. But installation of capacitor power bank leads to the increment of total harmonics distortion level. In common plant, containing power factor correction capacitor, It is been seen that normal resonant frequency falls normally in the range of 5th to 13th harmonics. So this non-linear load leads to inject current at 5th, 7th, 11th and 13th harmonics. It will usually result on producing the problems with switchgears, damaged capacitor banks and failure to the electrical distribution system.